Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.